Transfer coefficient measurements of uranium to the organs of Wistar rats, as a function of the uranium content in the food - Arruda-Neto, JDT; Likhachev, V. P.; Nogueira, G. P.; Araujo, G. W.; Camargo, S. P.; Cavalcante, G. T.; Cestari, A. C.; Craveiro, A. M.; Deppman, A.; Ferreira, J. W.; Garcia, F.; Geraldo, L. P.; et al. (Elsevier B.V., 2001)
Groups of animals (Wistar rats) were fed with rations doped with uranyl nitrate at concentrations ranging from 0.5 to 100 ppm. The uranium content in the ashes of the organs was measured by the neutron-fission track counting technique. The most striking result is that the transfer coefficients, as a function of the uranium concentration, exhibit a concave shape with a minimum around 20ppm-U for all organs. Explanations to interpret this finding are tentatively given. (C) 2001 Elsevier B.V. Ltd. All rights reserved.